The Need Analysis of Learning Materials for Teaching English for Specific Purpose at 2nd grade Computer Networking Students’ in SMKN 1 Bukittinggi - Tifannie Audya Syifa; Loli Safitri (English Language Teaching and Research, 2020)
This study analyzes needs of 2nd grade computer networking students at SMK 1 Bukittinggi because computer networking students desperately need English in accordance with their majors. In learning computer networking students of computer networking are still to uses English textbooks that have the same material as general students and this school has 6 majors. The subjects of this study were of 2nd grade computer networking   students. The researchers used a descriptive method which uses qualitative and quantitative paradigm. The populations of results of this study were all students of 2nd grade computer networking in SMK 1 Bukittinggi and the samples taken were all students of second grade computer networking with a total of 47 students and samples taken with proportional sampling techniques. The data collection technique used was a questionnaire. Researcher uses documents to collect data in analyzing the suitability of material in English and interview the English teacher that teaches of 2nd grade computer networking in vocational schools especially in SMKN 1 Bukittinggi. The   results of this study indicate that 2nd grade computer networking students need more specific English material for vocational students. Finally, ESP program is appropriate in vocational schools so students can understand English lesson.